2014
DOI: 10.1097/icu.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cataract surgery on glaucoma care

Abstract: Considering cataract surgery as an IOP-lowering procedure may be appropriate in select patients. Performing cataract extraction prior to glaucoma surgery has numerous benefits. The sequence of the procedures performed has implications in terms of complications, surgical success, and diagnostics. Reestablishing perimetric and structural baselines with imaging modalities is appropriate after cataract surgery is performed in glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Accurate identification of which patients will experience an IOP-lowering response could influence surgical decision-making, for instance determining when a cataract surgery alone would lower IOP adequately, or whether a concurrent glaucoma procedure is indicated [2, 14, 15]. Eyes with highest preoperative IOP have the greatest reduction in IOP in the long term [11].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate identification of which patients will experience an IOP-lowering response could influence surgical decision-making, for instance determining when a cataract surgery alone would lower IOP adequately, or whether a concurrent glaucoma procedure is indicated [2, 14, 15]. Eyes with highest preoperative IOP have the greatest reduction in IOP in the long term [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although these indexes are neither validated nor globally implemented, they might be helpful when making decisions regarding which surgical procedure to perform, whether a simple lens extraction would suffice to control the IOP or a more invasive (yet more effective) procedure would be necessary. Finally, many other biometric factors have been proposed as independent predictors of post-operative IOP - anterior chamber area, anterior chamber width, lens thickness - but their usefulness warrants further investigation [20,24,25]. …”
Section: Ocular Biometric Parametersmentioning
confidence: 99%
“…3 Strikingly, Ohsugi and associates 4 reported that choroidal thickness increased after cataract surgery and the changes in choroidal thickness were negatively correlated with IOP changes (early after surgery) and the axial length (in the late postoperative period). We also conducted research about choroidal thickness changes after cataract surgery and, consistent with Ohsugi and associates' findings, we found that phacoemulsification surgery causes a significant increase in the choroidal thickness, which is correlated with surgeryinduced IOP change in the short term (http://www.escrs.…”
Section: Editor: We Read With Great Interest the Original Article Bymentioning
confidence: 98%
“…2 Furthermore, it has been reported that hyperbaric oxygen can control inflammation and vasculogenesis by decreasing neutrophil adherence and downregulating the expression of intercellular adhesion molecule-1 and vascular endothelial growth factor. 3 Hyperbaric oxygen can improve the potency of antibiotics and has antibacterial effects as well. 4 Finally, hyperbaric oxygen stimulates the defense mechanisms against oxidative stress that plays a critical role in chemical injuries such as mustard-induced burns.…”
mentioning
confidence: 99%